Community forest enterprises (CFEs) as Social Enterprises: Empirical evidence from Cameroon - Piabuo, S.M.; Hoogstra-Klein, M.; Ingram, V.; Foundjem-Tita, D. (Elsevier, 2022)
Community forest enterprises (CFEs) trade to meet the economic, social, and environmental challenges of their community, just as Social Enterprises (SE) do. The question is if CFEs also could and should be understood in terms of SEs. To explore this question, this study determines the extent to which CFEs can be classified as SEs, using CFEs in Cameroon as a case study. Based on the three-dimensional EMES framework in combination with the typology of SEs of Alter, CFEs are classified along a continuum of purely non-profits, non-profits with income-generating activities, and SEs. Document review, interviews, and focus group discussions with CFE management, youths, women, and indigenous groups in 38 communities were used for data collection and subsequently analyzed. Of the 38 CFEs investigated, only 11% could be defined as SEs, 63% are non-profit organizations with income-generating activities and 26% operate as traditional non-profit organizations. The majority of the CFEs (63%) engage in commercial activities for revenue generation but lack the skills and organizational setup to employ full business approaches coupled with financial discipline and community ownership, which are core values of SEs. Operating as SEs would permit CFEs to be financially and environmentally sustainable and thus they could easily contribute to community development. However, moving CFEs from “non-profits with income generation” to SEs requires (i) a change in mindset, (ii) evaluation and building of community capacity for CFE development, (iii) proper research on tensions and paradoxes with actionable solutions, and (iv) sectorial coordination for CFE development, support, and creation of CFE incubation centers.